Biochemical characterization and Phylogroups of Escherichia coli isolated from feces of calves with diarrhea in the Cajamarca Region, Peru. - Cabrera–Gonzalez, M. (2022)
The objective of this research was the biochemical characterization and the identification of phylogroups in Escherichia coli strains, from feces of calves with diarrhea, using the Clermont method. Thirty-two samples were collected from eight herds from the Tartar Grande Hamlet, Baños del Inca District, Cajamarca Region, Peru. Through growth on MacConkey-MUG agar, thirteen samples were selected, characterized biochemically using the EnteroPluri®-Test kit and molecularly, the strains were identified by amplification of the uidA gene using the polymerase chain reaction (PCR) technique; the phylogroup was typified by Clermont quadruplex PCR. The isolated local strains showed a sorbitol and glucose fermenting biochemical profile, allowing them to be grouped and identified into five groups (codes 71340; 71350; 51340; 61740 and 61340); In addition, the uidA gene that encodes the beta-glucuronidase enzyme typical of the E. coli lineage was amplified. The identification of the phylogenetic group allowed to observe that they are grouped in group B1 (69.23 %), F (15.38 %), in addition to groups A (7.69 %) and D or E (7.69 %) respectively. It was achieved by amplification of the arpA, chuA, yjaA, TspE4.C2 genes. The local strains isolated from feces of calves with diarrhea represent naturalized bacterial populations adapted to the ecological niche of Cajamarca, having regional livestock as the main source of food for pastures, possibly contamination of these translates into an important means of transmission in calves for the presentation of colibacillosis, since these strains harbor the highest proportion of virulence genes.